Effect of Nicotine on Gallbladder Bile. (1st October 1994) - Anglo-Dutch Nicotine Intestinal Study Group,; Rhodes, Michael; Zijlastra, Freek J; Bradburn, D Michael; Srivastava, Emmanuel D; van Dijk, APM; Russell, Michael AH; Van Blankenstein, Mark; Wilson, JH Paul; Allen, Adrian; Rhodes, John
Abstract : Several studies have shown that symptomatic gallstones are largely a disease of nonsmokers, which raises the possibility that nicotine may protect against the formation of gallstones. To examine the effect of nicotine on the gallbladder, 32 rabbits were allocated to four groups: controls and three treatment groups in which nicotine tartarate at low, medium and high doses was administered subcutaneously via an osmotic minipump. After 14 days' treatment the gallbladder was removed and measurements made of gallbladder mucin synthesis, bile mucin concentration, bile acid concentration and cholesterol saturation. Serum nicotine concentrations (ng/mL) were (± SE) 0.4±0.1, 3.5±0.4, 8.8±0.8 and 16.2±1.8 in the controls and three treatment groups, respectively. Total bile acid concentration increased significantly in all three treated groups with the greatest increase in the group given low dose nicotine (P<0.001). Cholesterol saturation did not differ significantly in any group but soluble mucin concentration in gallbladder bile was significantly reduced (P=0.013, 95% CI: 16 to 111) with high dose nicotine. Gallbladder mucin synthesis, measured by 3 H-glucosamine incorporation, did not change significantly with nicotine treatment. Subcutaneous nicotine 2.0 mg/kg/day for 14 days significantly reduced the concentration of biliary mucin, which could potentially reduce cholesterol nucleation and subsequent gallstone formation. This may be one of the mechanisms responsible for the relative reduction in gallstone disease among smokers.